2011
DOI: 10.4038/cmj.v56i4.3897
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal injury suspected to be due to doxycycline ingestion

Abstract: Doxycycline induced oesophageal injury (DIEI) has contributed to 27% of the global burden of drug induced oesophageal injury. We report 21 cases of DIEI detected over a one year period.Cases were defined as sudden onset -chest pain, dysphagia and odynophagia within a few hours to days after taking doxycycline, confirmed by UGIE, with improvement on withdrawal of doxycycline. The majority was in the 20 -30 year age group and was female. The commonest symptoms were dysphagia and odynophagia. The mean time to sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 6 publications
2
13
0
1
Order By: Relevance
“…Allowing detection of the mucosal changes, taking biopsy sampling, and intervening in bleeding and other complications of the esophagus, upper endoscopy is the first choice for both diagnosis and the treatment (2,5,11,18). In the upper endoscopy, we found that most of the ulcers were located in the middle third of the esophagus, which is compatible with the literature (2,13). Although the histopathological examination of PE is rarely pathognomonic, it is generally nonspecific and includes mostly benign ulcer and acute inflammatory changes (12,16,(22)(23)(24).…”
supporting
confidence: 89%
See 4 more Smart Citations
“…Allowing detection of the mucosal changes, taking biopsy sampling, and intervening in bleeding and other complications of the esophagus, upper endoscopy is the first choice for both diagnosis and the treatment (2,5,11,18). In the upper endoscopy, we found that most of the ulcers were located in the middle third of the esophagus, which is compatible with the literature (2,13). Although the histopathological examination of PE is rarely pathognomonic, it is generally nonspecific and includes mostly benign ulcer and acute inflammatory changes (12,16,(22)(23)(24).…”
supporting
confidence: 89%
“…When the clinical presentations of the patients are taken into consideration, odynophagia, retrosternal pain, and dysphagia are the most encountered symptoms reported, with varying frequencies (2,6,8,11,13). In our study, the most frequent symptom was odynophagia, while hematemesis and melana were rarely primarily the reason for the application.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations